A novel method for predicting the occurrence of the large-scale shunting in the reverse-polarity plasma torch. (1st March 2023) - Yin, Zhengxin; Yu, Deping; Xiao, Yu; Zhang, Qingbo; Qiu, Jier
Abstract: The reverse-polarity plasma torch (RPT) is a promising high enthalpy plasma source for material processing, e.g. plasma atomization for spherical powders and plasma synthesis for the nanostructured carbon. The quality and yield of the final product highly depend on the working stability of the RPT, which may be undermined by the large-scale shunting. Large-scale shunting is an abnormal discharge phenomenon existed in the RPT, which leads to the sudden drop of the arc voltage and shrink of the generated plasma jet. Inter-electrodes between the cathode and anode are designed to limit arc fluctuations and thus large-scale shuntings. However, the construction and maintenance of the RPT with inter-electrodes are highly complex. To alleviate the large-scale shunting and retain the advantage of simple structure of the conventional RPT, a novel method for predicting the occurrence of the large-scale shunting is proposed for optimizing the RPT's internal structure and operation condition. The method is based on the thermal non-equilibrium modelling of the RPT to calculate the thickness of the cold boundary layer (CBL) and breakdown voltage. Then, the occurrence of the large-scale shunting is predicted by comparing the breakdown voltage with the voltage drop between the electrode inner surface and arc column. Three different shapes of the front electrode (cathode) corresponding to different thicknesses of the cold boundary layer (CBL) were manufactured based on the proposed numerical method. Experimental and numerical studies on the effect of the electrode geometry, arc current and gas flow rate on the working stability of the RPT and thickness of the CBL were conducted. Results showed the quantitative correlations between operating parameters and the instability of the RPT and verified that the proposed numerical method is useful for optimizing the design and operation of the plasma torch with minimizing large-scale shunting instabilities.